Evaluation of risk factors of premature coronary artery disease - M Vinod Kumar; Ganesh Rathod (Asian Journal of Medical Research, 2017)
Background: To evaluate risk factors of premature coronary artery disease. Methodology: Ninety cases of coronary artery disease of both genders were selected. Parameters such as family history, history of smoking, diabetes, obesity, high body mass index (BMI), high cholesterol, substance abuse was recorded. Echocardiography, serum lipid profile, complete hemogram, urine analysis, etc. were determined. Results: Out of 90 patients, males were 52 (57.7%) and females were 38 (42.3%). BMI found to be normal in 25 and overweight/ obese in 65 patients. 60 had positive family history, 54 were hypertensive, dyslipidaemia was present in 55, 58 were smokers, 48 were alcoholics and 34 were diabetics. The difference was significant (P< 0.05). Conclusion: Common risk factors in patients with premature coronary artery disease found to be positive family history, smoking, obesity, alcoholism, diabetes, dyslipidaemia and hypertension.